2021
DOI: 10.1007/s10551-021-04881-6
|View full text |Cite
|
Sign up to set email alerts
|

The Wealth Effect of Corporate Water Actions: How Past Corporate Responsibility and Irresponsibility Influence Stock Market Reactions

Abstract: Ensuring access to clean water is one of the most important development and health challenges of the twenty-first century. Given the manifold impacts of business activities on water resources, corporate water actions should be of central concern to business ethics researchers. Yet so far we know too little about whether business activities that impact on water resources are noticed or how corporate water actions are valued by a firm’s stakeholders, including by financial markets. In response, we conduct an eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Although this study is a response to calls for more empirical research on corporate water actions and the antecedents of corporate water usage (Afrin et al, 2021;Amran et al, 2014;Kurland & Zell, 2010;Whiteman et al, 2013), it suffers from data limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this study is a response to calls for more empirical research on corporate water actions and the antecedents of corporate water usage (Afrin et al, 2021;Amran et al, 2014;Kurland & Zell, 2010;Whiteman et al, 2013), it suffers from data limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a positive relationship between water usage reduction and financial performance (Chang & Liu, 2018), while others have documented no relationship between water usage and financial performance (Oberholzer & Prinsloo, 2011; Wagner, 2005). Recent evidence has addressed the implications for stock markets and revealed that investors react favorably (unfavorably) to responsible (irresponsible) water actions (Afrin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that water systems are now increasingly vulnerable and thus companies face serious physical, reputational, and regulatory water risks [ 5 , 6 ]. When companies internalize these risks, they already have significant implications for their business development [ 7 , 8 , 9 ]. However, most companies are still unaware of the risk and opportunities presented by water issues [ 10 ].…”
Section: Introductionmentioning
confidence: 99%